FAKTOR KEUANGAN PREDIKTOR FINANCIAL DISTRESS - Alviani, Erika; Syahzuni, Barlia Annis (Jurnal Riset Akuntansi Politala, 2025)
This study investigates the influence of profitability, liquidity, leverage, operating cash flow, and sales growth on financial distress, measured by the Z-Score, among Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. A sample of 63 companies was selected through purposive sampling, yielding 189 observations over three years. Employing a quantitative approach with multiple linear regression, the data met all classical assumption tests. Results show profitability and liquidity positively impact financial health, while leverage negatively affects it, increasing financial distress. However, operating cash flow and sales growth showed no significant effects. These findings provide insights for stakeholders in identifying key determinants of financial health to support strategic decision-making.